KERJA SAMA WHO - RI DALAM MENANGANI VIRUS POLIO DI INDONESIA MELALUI PROGRAM BEBAS POLIO - Yunita Astuti; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study describes the cooperation of World Health Organization (WHO) - Indonesia in dealing with polio in Indonesia through the program free of the disease. Health is one of the issues of international relations that are low politics that drew the world's attention, for example a health problem that is considered very important is the problem of polio. Indonesia is a country with endemic polio that makes WHO as an international health organization trying to solve this problem. The study was obtained by reviewing the literature either from books, journals, theses, reports, and internet. In this paper, the author uses pluralist perspective with international organizations theory. Author uses the analysis unit group as one actor in international relations. In the writings found that the cooperation of WHO - Indonesia in dealing with polio virus in Indonesia is to implement the program ERAPO. The program of ERAPO is to implemented National Immunization Week (PIN) and Polio Surveillance which includes Wild Polio Surveillance (SPL) and surveillance of Acute Flaccid Paralysis (SAFP). In addition, the Indonesian government is also carrying out immunization and vaccination. Keywords: World Health Organization (WHO), Indonesia, Cooperation, Polio, ERAPO